Hydronephrotic Kidney Assessment via Ultrasonography - Bhagwan Das, Kailash Kumar Daseja, Inayatullah, Muhammad Rashid Rasul, Akhtar Hussain Phul, Imran Khan Memon, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess hydronephrotic kidney assessment via ultrasonography. Study Design: Prospective study. Place and Duration of Study: Department of Radiology, Chandka Medical College Hospital, Larkana from 1st August 2020 to 31st September/2021. Methodology: Two hundred patients visited for the complaint and suspicion of hydronephrosis and within them 40 patients were diagnosed with hydronephrosis. The both kidneys were examined in the longitudinal as well as transvers planes of scanning using colored Doppler technique in ultrasonography. In older age patients a curved-array transducer having centered frequencies (3-6 MHz) was applied while in case of younger patients’ linear array-transducer was used with high entre frequencies. Results: The age of the patients was between 12-72 years with more elderly patients than youngsters. Most of the patients were males rather than females. Ureteropelvic obstruction in junction, primary megaureter as well as urethral valve involvement was observed in ultrasound imaging of hydronephrotic pediatric kidney. End stage hydronephrosis was presented in adult patients with cortical thining. Conclusion: Ureter and kidney stone appeared to be a common reason of hydronephrosis.